2000
DOI: 10.1111/j.1475-682x.2000.tb00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Marriage: An Examination of Opportunity Structures

Abstract: Though a number of authors have noted the increase in interracial marriages in the United States over the past few decades, few researchers have systematically examined variables that affect the opportunity for intergroup marriage among several different groups: Whites, African Americans, Asians, and Hispanics. In this paper we examine several “opportunity” variables and their relationship to intergroup marriage for couples age 40 or younger: immigration, military service, metropolitan residency, age, region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…By this logic, then, college-educated Latinas should have more opportunities to date "out" when they enter college and professional occupations where Latinos are few in number or non-Latinos are more abundant (Heaton and Jacobson 2007). Despite the link between exogamy and education, our findings reveal collegeeducated Latinas prefer dating "in" versus dating "out" and seek relationships with Latinos even if it means dating "down" or dating men with lower levels of educational attainment than they have.…”
Section: Latino Men Wantedmentioning
confidence: 97%
“…By this logic, then, college-educated Latinas should have more opportunities to date "out" when they enter college and professional occupations where Latinos are few in number or non-Latinos are more abundant (Heaton and Jacobson 2007). Despite the link between exogamy and education, our findings reveal collegeeducated Latinas prefer dating "in" versus dating "out" and seek relationships with Latinos even if it means dating "down" or dating men with lower levels of educational attainment than they have.…”
Section: Latino Men Wantedmentioning
confidence: 97%
“…Several descriptive studies have indicated (a) the more likely venues for the increase in opportunity and rate of interracial marriages were the military and college (Heaton & Jacobson, 2000); (b) finding a new couple identity as a result of the problems that cross-racial couples faced (Killian, 2001, p. 36); and (c) managing the criticism that interracial couples received from family, friends, and strangers (Datzman & Gardner, 2000). From the popular media and the professional literature have come some strong societal reactions to the race-crossing relationships of Black men and White women.…”
Section: Crossing the Color Line In Relationshipsmentioning
confidence: 97%
“…Researchers also have shown that opposition to BlackWhite marriage is much higher than marriage between other groups (e.g., Herring & Amissah, 1997;Lewis & Yancey, 1995;Spickard, 1989). Furthermore, the number of interracial marriages remains low, and it is far less than would be expected based on relative population sizes (Heaton & Jacobson, 2000;Qian, 1997).…”
mentioning
confidence: 89%